Profiles of success : a phenomenological study of successful PhD graduates - Erhijakpor, Perkins Shuaibu Orghenenyerhovwo (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study investigated the experiences during the PhD journey of eleven (11) successful PhD graduates at the IIUM Gombak and ISTAC campuses. The study employed a qualitative phenomenological research methodology. Data was elicited by oral interviews in an attempt to understand the meaning, structure and essence of success from the viewpoint of the PhD graduates. The data analysis was performed by clustering the interview data into significant statements and themes by means of Moustaka's (1994) phenomenological method. This was achieved by generating themes from the main ideas/concepts that are prevalent in the participants' views regarding their lived experience as they journeyed through their PhD. The findings unveiled that earning the PhD in the IIUM Gombak and ISTAC campuses involved diligent effort, unflinching determination, boundless patience, a strong iman and faith in Allah's limitless mercy, plus proper guidance from the supervisor and supervisory committee members, a supportive relationship with one's family members and friends, and a generous dose of good luck. Most successful PhD graduates agreed with the above findings, emphasising the need to maintain a well-balanced lifestyle and a positive attitude. In this respect, they particularly endorse the total commitment to adherence to the fundamental teachings and practices of Islam, cultivating the regular habit of praying for their own spiritual sustenance. In addition, most of them participate in some form of physical/sporting activity. They all concur that a good balance of physical, mental, and spiritual pursuits is essential to their well-being—especially their mental and emotional health. Most of the participants expressed the importance of social activities and interpersonal contacts to offset the loneliness and isolation resulting from long hours of working on the thesis/dissertation. Finally, successful PhD graduates share the opinion that it is imperative to set clear goals by seeking proper counselling preferably from their supervisor, and well-intentioned colleagues; diligence and strong self-discipline are necessary conditions, but the sufficient condition would include all of the above factors for a productive and successful PhD journey here at IIUM.